Amelioration of mitochondrial dysfunction-induced insulin resistance in differentiated 3T3-L1 adipocytes via inhibition of NF-kappa B pathways - Abu Bakar, M.H.; Sarmidi, M.R.; Kai, C.K.; Huri, H.Z.; Yaakob, H. (MDPI AG, 2014)
A growing body of evidence suggests that activation of nuclear factor kappa B (NF-kappa B) signaling pathways is among the inflammatory mechanism involved in the development of insulin resistance and chronic low-grade inflammation in adipose tissues derived from obese animal and human subjects. Nevertheless, little is known about the roles of NF-kappa B pathways in regulating mitochondrial function of the adipose tissues. In the present study, we sought to investigate the direct effects of celastrol (potent NF-kappa B inhibitor) upon mitochondrial dysfunction-induced insulin resistance in 3T3-L1 adipocytes. Celastrol ameliorates mitochondrial dysfunction by altering mitochondrial fusion and fission in adipocytes. The levels of oxidative DNA damage, protein carbonylation and lipid peroxidation were down-regulated. Further, the morphology and quantification of intracellular lipid droplets revealed the decrease of intracellular lipid accumulation with reduced lipolysis. Moreover, massive production of the pro-inflammatory mediators tumor necrosis factor-alpha (TNF-alpha) and interleukin-1 beta (IL-1 beta) were markedly depleted. Insulin-stimulated glucose uptake activity was restored with the enhancement of insulin signaling pathways. This study signified that the treatments modulated towards knockdown of NF-kappa B transcription factor may counteract these metabolic insults exacerbated in our model of synergy between mitochondrial dysfunction and inflammation. These results demonstrate for the first time that NF-kappa B inhibition modulates mitochondrial dysfunction induced insulin resistance in 3T3-L1 adipocytes.